Managing diversity : toward a globally inclusive workplace - Mor-Barak, Michàlle E. (SAGE Publications, Inc, 2017)
Successful management of a diverse workforce is one of the most important global challenges faced by corporate leaders, human resource managers, and management consultants. Offering original coverage of the historical and theoretical foundations that have led to today's practice of managing diversity in the workplace, this bestseller offers an original model for a globally inclusive workplace, bringing concepts to life with real-world situations. Key Features Demonstrates the benefits of implementing inclusive practices, complete with vignettes and case studies from around the world Explores the new realities of the workforce, including global demographic, legislative, and social policy trends Analyses the causes and consequences of workforce exclusion Provides a comprehensive model for an inclusive workplace with a fully utilized workforce.
Keywords: työpaikat; erilaisuus; johtaminen; moninaisuus; vähemmistöt; tasa-arvo; organisaatiokulttuuri; inkluusio; Diversity in the workplace